Barber Johnson Graph Efficiency Analysis - Erlangga Mandala Sakti; Byba Melda Suhita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to inform barber johnson graph efficiency analysis. This research method uses descriptive. The population and samples used are the entire census of inpatients from 2019 to 2021 at Siti Khodijah Muhammadiyah Gurah Pare Hospital. Data collection techniques are using, observing, interviewing, and counting. The data analysis technique used is by using the barber johnson formula. The results show that the calculation and analysis of the barber johnson graph efficiency 2019 to 2021 at Siti Khodijah Muhammadiyah Gurah Pare Hospital shows that the use of treatment bed at Siti Khodijah Muhammadiyah Gurah Pare Hospital is still not efficient, it is said to be inefficient because the meeting point of the 4 parameters barber johnson graph 2019 to 2021 is outside the efficient area, due to a reduction in bed resulting in the bed occupancy rate value also decreasing.